Medical ethics in the beginning of twentieth century. “The magic mountain” of Thomas Mann - Figueroa, Gustavo (Acta Bioethica, 2011)
Bioethics has deeply transformed medical ethics, appealing to other principles and practices. The present work tries to understand traditional western medical ethics by recurring to its description in artistic narrative, because this descri- bes with special quality and rigor the way it was understood and practiced before the bioethics turn. The work of Thomas Mann “The magic mountain” was chosen because, besides its intrinsic value, its point of view clears other moral foundations which could have been mal interpreted, disqualified or lost in the last years. Thus, the ethics of goodness predominated over the ethics of duty, the good life over obligation, self esteem over respect for the other, maximum achieved over minimum required. The acid critiques expressed by the omniscient narrator insinuate that this way of understanding moral behavior in medicine needs to complement other ethical views.